Incidence of Monochamus (Coleoptera: Cerambycidae) species in Nova Scotia, Canada Christmas tree plantations and comparison of panel traps and lures from North America and Europe. Issue 2 (1st November 2016) - Blatt, S.E.; Bishop, C.; Sweeney, J.
Abstract: Christmas trees from Nova Scotia, Canada are banned from import into the European Union (EU) because they may be infected with the pinewood nematode, Bursaphelenchus xylophilus (Steiner and Buhrer) Nickle (Nematoda: Parasitaphelenchidae). Monochamus Dejean (Coleoptera: Cerambycidae) species known to vector pinewood nematode are present in Nova Scotia but their abundance in Christmas tree plantations and surrounding stands has not been assessed. We conducted trapping surveys and experiments in 2014 and 2015 to determine the species of Monochamus and their relative abundance in Nova Scotia Christmas tree plantations and the surrounding forests. We also compared commercially available traps and lures from Europe (cross-vane traps, Galloprotect lure=monochamol+ipsenol+α-pinene+2-methyl-3-buten-2-ol) and North America (intercept panel traps, North American lure=monochamol+ipsenol+α-pinene+ethanol) for their efficacy at catching Monochamus species in a 2×2 factorial experiment. We captured three Monochamus species ( M. scutellatus (Say), M. notatus (Drury), and M. marmorator Kirby) in Nova Scotia Christmas tree plantations. Mean trap catches were greater within the plantations than in the surrounding forests. North American panel traps coated with Fluon ® and baited with the European lure caught the most M. notatus and M. scutellatus and would be most suitable for survey and monitoring.